Ultrasonographic evaluation in Brown Swiss cattle subjected to a heat synchronization protocol in the Peruvian highlands - Perez G., Uri (2019)
The follicular dynamics was evaluated by ultrasonography in Brown Swiss cattle subjected to a protocol of synchronization of estrus with progestogens in the Peruvian highlands. Three groups of Brown Swiss cattle of nine females each were evaluated. The groups were: lactating cows (<120 and >260 days in milk) and heifers. For synchronization, on day 0 a progesterone-based intravaginal device was applied, and 2 mg estradiol benzoate was injected, on day 8 the device was removed and 0.15 mg cloprostenol and 400 IU eCG were applied, and on day 10 1.05 mg GnRH was applied. Artificial insemination at fixed time was done 12 h after the application of GnRH. The ultrasound evaluation was done on days 8 and 10 to determine the growth rate and maximum diameter of the dominant follicle in the three groups. The follicular growth rate was 2.3 ± 1.5, 2.4 ± 1.8 and 2.3 ± 1.8 mm/day for the groups of lactating cows (<120 and >260 days in milk) and heifers, without significant difference between groups. The diameter of the dominant follicle was 14.5 ± 2.1 mm and 16.6 ± 3.1 mm in lactating cows (<120 and >260 days in milk, respectively) and 12.1 ± 2.0 mm in heifers, being significantly lower in heifers (p<0.05). The pregnancy rate was 44.4, 33.3 and 66.7% for lactating cows (<120 days, >260 days in milk) and heifers, respectively without significant difference between groups.